Descrição e avaliação de um modelo de serviço de dispensação de uma Farmácia Universitária em Goiânia, Goiás, Brasil - Ferreira, Tatyana Xavier Almeida Matteucci (2013)
Background: Although dispensing of medication has been addressed on theoretical models, studies that confirm the impact of this service are still needed. Objective: to describe and evaluate a model of medicine dispensing developed and implemented in a pharmacy in accordance with the parameters of structure, process and outcome. Methods: This was a descriptive, observational and quasi-experimental study performed in a Campus Pharmacy, approved by the Ethics Committee in Research of the Federal University of Goiás under protocol 222/2012. one hundred and four patients attending the dispensing service of the campus pharmacy between 21 January 2013 and 20 April 2013 were included in this quasi-experimental study. The description and assessment of the service was performed in terms of the three parameters: structure, process and outcome, used by Donobedian to evaluate the quality of medical care and adapted by Farris & Kirking to evaluate the quality of pharmaceutical care. The description and assessment of each parameter was performed as recommended by the Ministry of Health of Brazil, international agencies and previous studies. Assessment of knowledge about medicine prescription and adherence, before and after medicine dispensing, was performed by McNemar’s test. Associations between variables were assessed by the Wald test. A p-value <0.05 was considered to be statistically significant. Results: Medicine dispensing improved patient’s knowledge about medications (P<0.05), which was associated with pharmacotherapy complexity (P<0.05). The main problems identified were related to lack of patient’s knowledge regarding their medication (52.9%). Pharmaceutical interventions were mostly performed directly to the patients (86.3%) by verbal (95.4%) and written (68.2%) information, and most of the problems were completely solved (62.7%). Pharmacy service was evaluated as “excellent” or “very good” by more than 70% of patients, and a high level of satisfaction was observed. Improvement of medication adherence, however, was not observed. Conclusion: the medicine dispensing model was able to identify and solve drug-related problems and promote an improvement in patient’s knowledge about medication.